Antimicrobial effect of OKCEL® H-D prepared from oxidized cellulose - Moťková, Petra; Brožková, Iveta; Vytřasová, Jarmila; Kukla, Rudolf (Folia microbiologica, 2018)
The antimicrobial effect of OKCEL® H-D, a topical, absorbable hemostatic textile prepared from oxidized cellulose, was tested. Testing by dilution and diffusion methods was conducted on a spectrum of 27 select microorganisms, including also antibiotic-resistant strains. OKCEL® H-D showed inhibitory effects on nearly all tested bacteria. In testing using the dilution suspension method, the majority of bacteria showed decrease in cell density by 7-8 orders of magnitude after just 6 h of exposure. For clinical isolates of antibiotic-resistant strains, a reduction occurred after 24 h of exposure. In testing the antimicrobial effects of OKCEL® H-D by the dilution method was least effective on spore-forming Bacillus subtilis, for which no antimicrobial effect was detected after 48 h, and on Mycobacterium smegmatis, for which the number of cells decreased by four orders of magnitude only after 24 h. By the diffusion method, inhibition zones were recorded for nearly all test microorganisms except for Staphylococcus aureus, M. smegmatis, and Listeria monocytogenes. No growth beneath the tested OKCEL® H-D material was recorded, however, even for the latter-named bacteria strains, which attests to its good inhibitory effect.
Keywords: Listeria monocytogenes; Bacillus subtilis; Drug Resistance, Bacterial; antibakteriální látky; Microbial Sensitivity Tests; Cellulose, Oxidized; Anti-Bacterial Agents; Staphylococcus aureus; bakteriální léková rezistence; mikrobiální testy citlivosti; celulosa oxidovaná